Hemiface Differences in Visual Exploration Patterns When Judging the Authenticity of Facial Expressions - Busin, Yuri; Lukasova, Katerina; Asthana, Manish K.; Macedo, Elizeu C. (Frontiers in Psychology, 2018)
Hemiface differences in visual exploration patterns when judging the authenticity of facial expressions. Hemiface differences in emotions judgment. Yuri Busin1, Katerina Lukasova2*, Manish Kumar Asthana3, Elizeu Coutinho Macedo1 1. Social and Cognitive Neuroscience Laboratory, Mackenzie Presbyterian University, Sao Paulo, Brazil 2. Center for Mathematics, Computation and Cognition (CMCC), Federal University of ABC (UFABC), Sao Bernardo, Brazil 3. Department of Humanities and Social Sciences, Indian Institute of Technology Kanpur, Kanpur, India Corresponding author: Katerina Lukasova; Social and Cognitive Neuroscience Laboratory and Developmental Disorders Program, Center for Health and Biological Sciences, Mackenzie Presbyterian University, Rua Piaui, 181, 10th Floor, São Paulo, SP, 01241-001, Brazil E-mail: katerinaluka@gmail.com Abstract Past studies have found asymmetry biases in human emotion recognition. The left side bias refers to preferential looking at the left-hemiface when actively exploring face images. However, these studies have been mainly conducted with static and frontally oriented stimuli, whereas real-life emotion recognition takes place on dynamic faces viewed from different angles. The aim of this study was to assess the judgment of genuine vs. masked expressions in dynamic movie clips of faces rotated to the right or left side. Forty-eight participants judged the expressions on faces displaying genuine or masked happy, sad, and fearful emotions. The head of the actor was either rotated to the left by a 45o angle, thus showing the left side of the face (standard orientation), or inverted, with the same face shown from the right side perspective. The eye movements were registered by the eye tracker and the data were analyzed for the inverse efficiency score, the number of fixations, gaze time on the whole face and in the regions of interest (ROI). Results showed shorter inverse efficiency scores and gaze times for happy compared to sad and fearful emotions, but no difference was found for these variables between sad and fearful emotions. The left side preference was evident from comparisons of the number of fixations. Standard stimuli received a higher number of fixations than inverted ones. However, gaze time was long on inverted compared to standard faces. Number of fixations on exposed hemiface interacted with the emotions decreasing